Evaluation of Erosion and Friction Wear of Ductile Material - Chawla, Kapil (My University, 2012)
Wear is the loss of material from a component due to a mechanical interaction with another object. Wear is one of the most common problem encountered in industries like thermal power plants, hydropower plants, mining industries, food-processing industries etc. in which solid liquid mixture is transported through pumps and pipes and also in the mechanical components which slides over another such as ball bearing, cylinder head and piston of the engine. Erosion wear is due to exposure to moving liquids and gases, which may or may not contain hard particulate. Effect of wear in slurry pumps, pipes, and in mechanical component is predominantly more as compared to corrosion. The service life of equipment of slurry transport system and several mechanical components is reduced by erosion caused by solid-liquid mixture following through the slurry transport system or friction caused by when one element slides over another element. My present work is to study the wear behavior of ductile materials. Stainless steel 304 and grey cast iron taken for the study of erosion wear of pump and piping system with fly and bottom ash slurry. And same material are taken to calculate friction behavior as they used in steel 304 used in ball bearing and grey cast iron used in making cylinder head .To improve the wear resistance of stainless steel 304 and grey cast iron, chromium oxide powder coatings were done by electroplating coating method. The erosion wear evaluated with varying the parameters like concentration, speed and time using erosion pot tester TR-41. It is observe that both coatings shows better performance than uncoated steel and grey cast iron in all conditions in which erosion wear test was performed. Friction wear was calculated using pin on disc apparatus for both uncoated materials at different parameters such as speed, load, and time. The maximum erosion wear reported by stainless steel 304 as compared to grey cast iron and chromium oxide coating shows better wear resistance. But in friction wear grey cast iron shows better wear resistance as compared to the steel 304. Erosion wear of both coated and uncoated steel increases with increase in concentration, time and speed.
M.Tech. (Production and Industrial Engineering)
Keywords: Erosio wear; slurry; friction wear